PERAN PENYULUH PERTANIAN DALAM MENINGKATKAN AKSES PASAR PETANI CABAI RAWIT DI DESA MATABURA KECAMATAN AMONGGEDO KABUPATEN KONAWE - Claudia, Priska; Rianse, Usman; Arif, La Ode Kasno (Jurusan Penyuluhan Pertanian FP UHO, 2026)
The present study explores the untapped potential of developing cayenne pepper as a strategic horticultural commodity in Matabura Village, Amonggedo District, Konawe Regency. The analysis reveals that this potential has not been realized due to several constraints. First, farmers' knowledge, bargaining position, and technology utilization are inadequate. Second, the role of agricultural extension workers in supporting marketing and enhancing farmers' welfare is suboptimal. The objective of this study is to ascertain the role of agricultural extension workers, the market access of cayenne pepper farmers, and the relationship between the role of agricultural extension workers and the market access of cayenne pepper farmers in Matabura Village. The present study employs a quantitative approach, utilizing an explanatory survey design. The study population consists of all cayenne pepper farmers who actively participate in agricultural extension activities in Matabura Village, with a total of 26 individuals included in the study. The present study employed a census technique. The data collection process entailed the implementation of various methodologies, including surveys, interviews, and documentation. The research variables of interest were the role of agricultural extension workers and market access. Quantitative descriptive methods were used to analyze the data. The results demonstrated that the role of agricultural extension workers in Matabura Village was relatively effective and contributed significantly to improving the market access of cayenne pepper farmers. Extension workers have performed a variety of strategic functions, including roles as educators, information disseminators, motivators, and facilitators. These functions have included the provision of training, market and price information, marketing assistance, and the strengthening of business networks and partnerships. The market access of cayenne pepper farmers is also favorable, as evidenced by the availability of marketing facilities and cooperation with various parties. However, this is not yet universally experienced by all farmers. The correlation test results show a positive and strong relationship between the role of agricultural extension workers and farmers' market access (r = 0.770; p < 0.05), confirming that optimizing the role of extension workers is a key factor in expanding market access and improving farmers' bargaining position. Strengthening the capacity and institutional support of extension services needs to be continuously improved to encourage more sustainable agricultural marketing.